Blockchain and Cryptocurrencies - Nadarajah, Saralees; Chan, Stephen; Chu, Jeffrey; Zhang, Yuanyuan; Nadarajah, Saralees; Chan, Stephen; Chu, Jeffrey; Zhang, Yuanyuan (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Blockchain and cryptocurrencies have recently captured the interest of academics and those in industry. Cryptocurrencies are essentially digital currencies that use blockchain technology and cryptography to facilitate secure and anonymous transactions. The cryptocurrency market is currently worth over $500 billion. Many institutions and countries are starting to understand and implement the idea of cryptocurrencies in their business models. This Special Issue will provide a collection of papers from leading experts in the area of blockchain and cryptocurrencies. The topics covered in this Special Issue will include but are not limited to the following: academic research on blockchain and cryptocurrencies; industrial applications of blockchain and cryptocurrencies; applications of fintech in academia and industry; the economics of blockchain technology, and the financial analysis and risk management with cryptocurrencies.
English
Keywords: Technology: general issues; cryptocurrencies; connectedness; spill overs; spectral analysis; time-frequency-dynamic; Bitcoin; cryptocurrency; spillover risks; Copulas; Student$1 (Bs-ts; survey; bitcoin; efficient market hypothesis; ARIMA; artificial neural network; static forecast; contagion effect; detrended cross-correlation analysis; liquidity; Ethereum; market liquidity; Hurst exponent; high frequency; fraud; algorithms; correlations; impact; risks; regulation; blockchain; autoregression; time-series analysis; simulation; predictive modes; endogenous; exogenous variables; Blockchain; Cryptocurrencies; Digital Currencies; Risk management; Financial analysis